Genes Bound by ΔFosB in Different Conditions With Recurrent Seizures Regulate Similar Neuronal Functions - Stephens, Gabriel S.; Fu, Chia-Hsuan; St. Romain, Corey P.; Zheng, Yi; Botterill, Justin J.; Scharfman, Helen E.; Liu, Yin; Chin, Jeannie (Frontiers in Neuroscience, 2020)
Seizure incidence is increased in Alzheimer’s disease (AD) patients and mouse models, and treatment with the antiseizure drug levetiracetam improves cognition. We reported that one mechanism by which seizures can exert persistent effects on cognition is through accumulation of ∆FosB, a transcription factor with a long half-life. Even the infrequent seizures that spontaneously occur in transgenic mice expressing human amyloid precursor protein (APP) lead to persistent increases in ∆FosB in the hippocampus, similar to what we observed in patients with AD or temporal lobe epilepsy. ∆FosB epigenetically regulates expression of target genes; however, whether ∆FosB targets the same genes when induced by seizures in different neurological conditions is not clear. We performed ChIP-sequencing to assess the repertoire of ∆FosB target genes in APP mice and in pilocarpine-treated wildtype mice (Pilo mice), a pharmacological model of epilepsy. These mouse models allowed us to compare AD, in which seizures occur in the context of high levels of amyloid beta, and epilepsy, in which recurrent seizures occur without AD-specific pathophysiology. Network profiling of genes bound by ∆FosB in APP mice, Pilo mice, and respective control mice revealed that functional domains modulated by ∆FosB in the hippocampus are expanded and diversified in APP and Pilo mice (vs respective controls). Domains of interest in both disease contexts involved neuronal excitability and neurotransmission, neurogenesis, chromatin remodeling, and cellular stress and neuroinflammation. To assess the gene targets bound by ∆FosB regardless of seizure etiology, we focused on 442 genes with significant ∆FosB binding in both APP and Pilo mice (vs respective controls). Functional analyses identified pathways that regulate membrane potential, glutamatergic signaling, calcium homeostasis, complement activation, neuron-glia population maintenance, and chromatin dynamics. RNA-sequencing and qPCR measurements in independent mice detected altered expression of several ∆FosB targets shared in APP and Pilo mice. Our findings indicate that seizure-induced ∆FosB can bind genes in patterns that depend on seizure etiology, but can bind other genes regardless of seizure etiology. Understanding the factors that underlie these differences, such as chromatin accessibility and/or abundance of co-factors, could reveal novel insights into the control of gene expression in disorders with recurrent seizures.